The Effect Of Knowledge And Skills On Employee Performance At PT. Graha Informatika Nusantara Tap Ajamu Labuhan Batu - Siti Hamidah (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2022)
This study aims to determine the effect of knowledge and skills on employee performance at PT. Graha Informatika Nusantara Tap Ajamu Labuhan Batu. This study uses a quantitative descriptive approach, aiming to determine the relationship between two or more variables. The population of this research is the employees of PT. Graha Informatika Nusantara Tap Ajamu Labuhan Batu as many as 60 employees. The sample in this study were 60 employees of PT. Graha Informatika Nusantara Tap Ajamu Labuhan Batu. The analysis technique used is multiple regression analysis. The suitability test using the t test and F test was conducted to test the effect partially and simultaneously between the independent variable and the dependent variable with the assumption that other variables are considered constant. Based on the results of the partial test, it is known that the Knowledge (X1) and Skills (X2) variables have an influence on Employee Performance (Y). Based on the results of the F test, the calculated f value is 32.743 with a sig level of 0.000, therefore the sig value is 0.000 > 0.05 and the calculated F value is 32.743 > F table 3.16. This shows that Ho is rejected, so it can be concluded that the independent variables X1, and X2 are independent. simultaneous positive and significant effect on the dependent variable Y. Based on the results of the coefficient of determination the value of Adjusted R square is 0.518. This means that the effect of variable X on variable Y is 51.8%, while the remaining 0.482 or 48.2% is influenced by other variables not included in this study.